Halogenated Alkyltetrazoles for the Rational Design of FeII Spin‐Crossover Materials: Fine‐Tuning of the Ligand Size. Issue 20 (9th January 2018) - Müller, Danny; Knoll, Christian; Seifried, Marco; Welch, Jan M.; Giester, Gerald; Reissner, Michael; Weinberger, Peter
Abstract: 1‐(3‐Halopropyl)‐1 H ‐tetrazoles and their corresponding Fe II spin‐crossover complexes have been investigated in a combined experimental and theoretical study. Halogen substitution was found to positively influence the spin transition, shifting the transition temperature about 70 K towards room temperature. Halogens located at the ω position were found to be too far away from the coordinating tetrazole moiety to have an electronic impact on the spin transition. The subtle variation of the steric demand of the ligand in a highly comparable series was found to have a comparatively large impact on the spin‐transition behavior, which highlights the sensitivity of the effect to subtle structural changes. Abstract : Steric fine‐tuning : 1‐(3‐Halopropyl)‐1 H ‐tetrazoles and their corresponding Fe II spin‐crossover complexes have been investigated in a combined experimental and theoretical study. Halogen substitution of 1‐(propyl)‐1 H ‐tetrazole has been found to shift the spin‐transition temperature by about 70 K towards room temperature (see figure). The reason for this impact was found to lie in the steric fine‐tuning of the ligand backbone.